Respon Pasar Saham Terhadap Kurs, Harga Emas dan Inflasi di Indonesia (Jurnal Simki Economic, 2024)
The financial market is the driving force of the country's economy because it can be used as an instrument for capital formation, facilitating community participation in resource mobilization, and facilitating financing for national development. This study examines the stock market response to the exchange rate, gold prices and inflation in Indonesia. This research uses quantitative methods with secondary data collection methods for the period June 2016 – July 2023. Data processing was carried out using a multiple linear regression analysis model. The results show that the Indonesian stock market responded positively to changes in the exchange rate, namely 36.244. Meanwhile, the price of gold was also responded positively by the Indonesian stock market at 0.532, while inflation was responded negatively by the Indonesian stock market at 0.253. Thus, the Indonesian stock market responds to every change in variables such as the exchange rate, gold prices and inflation.